2020
DOI: 10.3390/s20030934
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Air Purification: A Study on Volatile Organic Compounds in a Gas Cell

Abstract: Air pollution is one of the major environmental issues that humanity is facing. Considering Indoor Air Quality (IAQ), Volatile Organic Compounds (VOCs) are among the most harmful gases that need to be detected, but also need to be eliminated using air purification technologies. In this work, we tackle both problems simultaneously by introducing an experimental setup enabling continuous measurement of the VOCs by online absorption spectroscopy using a MEMS-based Fourier Transform infrared (FTIR) spectrometer, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The MEMS-based FTIR spectrometer (Neospectra, Si-Ware Systems), developed by our group, uses a MEMS-based Michelson interferometer deeply etched on a silicon substrate using the deep reactive ion etching technique, a long travel range actuator, and a lead selenide (PbSe) detector. This enables it to acquire spectra at a resolution of 66 cm –1 in the wavelength range 1350–4500 nm (wavenumber range 2500–7400 cm –1 ), which includes only the beginning of the mid-infrared range (larger wavenumbers), in contrast to other techniques such as quantum cascade laser-based systems that measure in the middle of the infrared region.…”
Section: Methodsmentioning
confidence: 99%
“…The MEMS-based FTIR spectrometer (Neospectra, Si-Ware Systems), developed by our group, uses a MEMS-based Michelson interferometer deeply etched on a silicon substrate using the deep reactive ion etching technique, a long travel range actuator, and a lead selenide (PbSe) detector. This enables it to acquire spectra at a resolution of 66 cm –1 in the wavelength range 1350–4500 nm (wavenumber range 2500–7400 cm –1 ), which includes only the beginning of the mid-infrared range (larger wavenumbers), in contrast to other techniques such as quantum cascade laser-based systems that measure in the middle of the infrared region.…”
Section: Methodsmentioning
confidence: 99%
“…[128] Fathy et al used a MEMS-based FTIR spectrometer with a length of only 10 cm for air purification monitoring. [137] They use a modified version of the Neospectra MEMS spectrometer to analyze in the midinfrared region. [129] Due to the spectrometer's relatively low resolution (50 cm À1 ), it was not possible to distinguish between acetone and toluene.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…At the end of the growing process, the Si substrates covered by ZnO NWs were washed with DI water, dried under hot airflow (~30 s at ~53 • C), and post-annealed in an oven at 350 • C for 30 min in ambient atmosphere to improve the ZnO crystallinity. Scanning electron microscope images (SEM, Zeiss FE-SEM NEON 40, Iéna, Germany) demonstrated that well organized and homogeneous ZnO NWs grown onto Si (1.55 cm 2 ) were obtained, with a measured height of 1.10 ± 0.05 µm and a measured mean diameter of 85 ± 5 nm in concentration conditions (C1) and a measured height of 1.80 ± 0.1 µm and a measured mean diameter of 51 ± 5 nm in concentration conditions (C2) [24,25]. Previous characterization works also proved the good crystallinity of the as-obtained ZnO NWs by ultraviolet-visible spectrophotometry (Maya2000 Pro from Ocean Optics, Dunedin, FL, USA), with a mean measured gap value around 3.21 ± 0.03 eV, and by X-ray diffraction (XRD, CuKα, λ = 1.5418 Å, Rigaku Smartlab, Neu-Isenburg, Germany), with ZnO Wurtzite peaks obtention [22][23][24][25].…”
Section: Engineering Materials Functionalizationmentioning
confidence: 99%